Studi kasus pertumbuhan ikan lele (Clarias gariepinus) yang dibudidayakan oleh masyarakat Desa Oelbubuk, Desa Haumenibaki Di Kabupaten Timor Tengah Selatan - Funome, Imanuel Vito Pratama; Rebhung, Felix; Liufeto, Franchy Ch (Jurnal Aquatik, 2024)
The African catfish (Clarias gariepinus) presents an opportunity for cultivation due to its rapid growth and high adaptability, making it a common choice for both industrial and household cultivation. This study aims to assess the growth and survival rates of African catfish (C. gariepinus) and compare these metrics between different groups. The research, spanning one month, will be conducted in two villages, Oelbubuk Village and Haumenibaki Village, located in the South Central Timor Regency. The methodology involves direct observation and sampling, with 100 catfish fry samples collected from each location, ranging in size from 5 to 9 cm. Parameters measured include growth in weight and absolute length, survival rates (SR), and water quality. Data collected will be analyzed descriptively and presented in tabular format. Preliminary findings indicate favorable growth and survival rates in Haumenibaki Village. Keywords: Survival rate, catfish and growth